Activation of persons living with HIV for treatment, the great study. (December 2015) - Fiscella, Kevin; Boyd, Michele; Brown, Julian; Carroll, Jennifer; Cassells, Andrea; Corales, Roberto; Cross, Wendi; El'Daher, Nayef; Farah, Subrina; Fine, Steven; Fowler, Richard; Hann, Ashley; et al.
Abstract Background Patient empowerment represents a potent tool for addressing racial, ethnic and socioeconomic disparities in health care, particularly for chronic conditions such as HIV infection that require active patient engagement. This multimodal intervention, developed in concert with HIV patients and clinicians, aims to provide HIV patients with the knowledge, skills, attitudes and tools to become more activated patients. Methods/Design Randomized controlled trial of a multimodal intervention designed to activate persons living with HIV. The intervention includes four components: 1) use of a web-enabled hand-held device (Apple iPod Touch) loaded with a Personal Health Record (ePHR) customized for HIV patients; 2) six 90-minute group-based training sessions in use of the device, internet and the ePHR; 3) a pre-visit coaching session; and 4) clinician education regarding how they can support activated patients. Outcome measures include pre- post changes in patient activation measure score (primary outcome), eHealth literacy, patient involvement in decision-making and care, medication adherence, preventive care, and HIV Viral Load. Discussion We hypothesize that participants receiving the intervention will show greater improvement in empowerment and the intervention will reduce disparities in study outcomes. Disparities in these measures will be smaller than those in the usual care group. Findings have implications for activating persons living with HIV and for other marginalized groups living with chronic illness. Trial registration ClinicalTrials.gov Identifier:NCT02165735, 6/13/2014.